Early Bronze Age obsidian networks: A view from Project ArAGATS - Smith, Adam T. (ARAMAZD: Armenian Journal of Near Eastern Studies, 2022)
As a testimonial to Ruben Badalyan’s indelible contributions to the archaeology of the South Caucasus, this paper presents the results of a portable X-ray fluorescence study of a large sample of securely provenienced Early Bronze Age obsidian artifacts and debris from the excavations of Project ArAGATS, the collaborative program of archaeological research that we co-founded a quarter of a century ago. Statistical analyses were performed on a corpus of 467 pXRF assays of materials from the sites of Gegharot and Aragatsi Berd, located on the northeast flank of the Tsaghkahovit Plain of central Armenia. The results shed important new light on changing resource exploitation strategies over time that may be indices of variable homelands for Gegharot’s settlers. Moreover, variation in exchange networks across Gegharot’s topographically defined sectors indicate differential participation in regional exchange networks by contemporaneous households. Taken together, the results of this study indicate that the material homogeneity of Kura-Araxes villages like Gegharot need not suggest a lack of variability in daily experiences, social networks, and exchange relationships.